Specificity of bioethics committees’ formation: political and institutional aspect - Здорик, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The rapid development of science has significantly expanded the boundaries of liberal discourse, by including bioethics to it. Bioethics has special status due to the fact that unlike other sectors of ethics within it specifically organized structures that affect the implementation of the relevant norms are formed. It is about bioethical committees as basic structural components of bioethics, becoming the subject exactly in the political and institutional dimensions. Specificity of the institutionalization of bioethics committees became the subject of analysis in this article, in particular, a comparison of European and American experience of their formation. The role of bioethics committees primarily is to promote the transformation of informal sanctions into formal and commonly used.